Women and War: Exposing Palestinian Women Resistance Through Literary Work - Utami, Shinta Fitria; Riza, Yulfira; Nur Wijaya, Taufik Amin (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2024)
Warfare is often associated with masculinity, leading to the absence of women’s roles during times of war. This phenomenon also occurs in the Palestinian conflict, where narratives related to the resistance of Palestinian women are frequently overlooked. As a direct reflection of life, literary works capture the reality of Palestinian women’s resistance. Therefore, this research aims to expose the resistance of Palestinian women as reflected in an Arabic novel titled al-Ṭanṭūriyyah by Raḍwā ‘Āṣūr. This study is a library research with a descriptive analytical approach. It utilizes Hélène Cixous’s ideas regarding the binary opposition of patriarchy. The research data is derived from words, phrases, and sentences in the novel al-Ṭanṭūriyyah that narrate the resistance of Palestinian women. Data collection begins with intensive reading techniques to ensure a comprehensive understanding. Subsequently, the data is categorized according to the topics of discussion. The data analysis process involves contextual investigation to strengthen primary data through supporting literatures and scholarly articles. The research findings indicate that Palestinian women indeed live under the shadow of patriarchal culture. However, they also actively participate in resistance against Israeli occupation. Their resistance involves non-violent actions such as aiding war accommodations, writing, and engaging in protests. Additionally, they resist through military and political means